ACUTE KIDNEY INJURY IN PREGNANCIES COMPLICATED WITH PRE-ECLAMPSIA OR HELLP SYNDROME: A RETROSPECTIVE STUDY. - Suman, Akanksha; Sinha, Sangeeta (Student's Journal of Health Research Africa, 2023)
Background This study aimed to determine the prevalence of Acute Kidney Injury (AKI) and its clinical characteristics and outcomes among pregnant women in the Indian state of Bihar with pre-eclampsia or Hemolysis, Elevated Liver Enzymes, and Low Platelet (HELLP) syndrome. Methods A retrospective unit study was conducted at tertiary care facilities in Bihar on women diagnosed with pre-eclampsia or HELLP syndrome during pregnancy. All the gathered data, including demographic information, obstetric history, test results, and maternal and foetal outcomes, originated from medical records. A statistical analysis was conducted on the incidence rates of AKI and the associated risk variables. Results One hundred pregnant women participated in this study, in which 15% of pregnant participants with pre-eclampsia or HELLP syndrome, suffered with acute kidney damage. Acute kidney damage risk factors include maternal age over 35, first-time pregnancy, severe hypertension, and delayed antihypertensive drug initiation. Acute renal injury caused respiratory distress, pulmonary oedema, and dialysis in mothers. AKI-compromised pregnancies exhibited more significant rates of preterm birth, low birth weight, and perinatal mortality. Conclusion Pregnant women in Bihar with pre-eclampsia or HELLP syndrome have a significant rate of AKI. First, identify risk variables and then quickly apply management techniques to avoid and control AKI in this population. Prenatal care, regular blood pressure monitoring, and early antihypertensive treatment are crucial to lowering AKI prevalence and severity. Recommendation For improved management of AKI in expectant women with pre-eclampsia or HELLP syndrome, blood pressure and urine protein levels should be routinely monitored as part of prenatal care. Protect against AKI by initiating antihypertensive treatment promptly and promoting interdisciplinary collaboration for the overall management of high-risk pregnancies. Promote research and surveillance to evaluate and improve current AKI preventive measures, and establish long-term follow-up programmes to assess postpartum kidney health.